ZOON POLITICON SYNDROME IN MODERN SOCIETY AS REPRESENTED IN AKEELAH AND THE BEE (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2013)
The study of Zoon Politicon Syndrome as Represented in Akeelah and the Bee is carried out to find out how modern society is represented in the novel Akeelah and the Bee and to describe how the modern society in the novel reflects signs of zoon politicon syndrome. There are several research methods used in this study, they are library research and descriptive qualitative research. By using library research method, I found the data and references dealing with the topic analysis. The data then written in descriptive and in order to answer the research questions, I also employ psychological approach. It is done to analyze how the modern society as represented in its intrinsic elements and how the modern society reflects signs of zoon politicon syndrome. The results indicate that the modern society is represented by three major groups. They are functional (ascription and acquisistion), aggregate, and category groups. The functional ascription covers the family group and the acquisition is represented by Terrencewho joined Derrick-T’s gangbang. Then the aggregate is portayed by the audience of the spelling bee. The last is the category which is represented by the  Hispanic, African-American.There are many kinds of groups in society and each group has its own rules and norms. Zoon politicon syndrome happens when the group can push the members to keep align the members with its rules and norms. The signs of zoon politicon syndrome is represented by Akeelah,Terrence, and Mr. Welch. Akeelah who tried not to look smart and Terrence who aped Derrick-T’s clothes and mannerism in order not to be bullied and accepted in the society. The other sign is when Mr. Welch forced Akeelah to join competition with his power as a headmaster.